Never Too Old for Congenital Heart Disease: Sinus Venosus Atrial Septal Defect with Anomalous Pulmonary Venous Return in an Octogenarian. (September 2015) - Sharma, Ravi K.; Houston, Brian A.; Lima, João A. C.; Cameron, Duke E.; Tedford, Ryan J.
We report a rare case in an 86-year-old woman with symptoms of exercise intolerance, fatigability, worsening lower extremity edema, and normal ejection fraction on echocardiographic examination who presented with a presumptive diagnosis of heart failure with preserved ejection fraction (HFpEF). Hemodynamic studies revealed that she had normal left-sided filling pressures, mildly elevated pulmonary pressures with normal pulmonary vasculature resistance, and evidence of right ventricular dysfunction. Significant shunting was also detected with a step-up blood oxygen saturation from superior vena cava to right atrium and a calculated pulmonary-to-systemic blood flow ratio of 3.9. Contrast-enhanced multidetector cardiac computed tomography confirmed the presence of a patent foramen ovale, a sinus venosus atrial septal defect, and 3 anomalous pulmonary venous communications to the right atrium and superior vena cava. We hereby present one of the oldest diagnosed cases of sinus venosus defect with anomalous pulmonary venous return as a rare cause of recent-onset dyspnea, volume overload, and functional intolerance in an 86-year-old woman with an initial misdiagnosis of HFpEF.